Prevalence of Visual Impairment Among Students Before and During the COVID-19 Pandemic, Findings From 1,057,061 Individuals in Guangzhou, Southern China - Liang, Jing-hong; Chen, Yi-can; Zhao, Yu; Kakaer, Aerziguli; Jiang, Nan; Huang, Shan; Zhang, Shu-xin; Chen, Ya-jun (Frontiers in Pediatrics, 2022)
Background: Visual impairment(VI) is a growing public health concern among students as a result of the COVID-19 pandemic. Objective: This study investigated the change in VI before and during the pandemic among students. Methods: Data on 547,864 and 497,371 students were obtained from the Guangzhou Survey on Students’ Constitution and Health(GSSCH) collected in October 2019 and October 2020, respectively. Visual impairment was defined as the unaided distance visual acuity lower than 20/25 Snellen equivalent(LogMAR 0.10) in the worse eye. Change in VI based on age and sociodemographic variables were evaluated by chi-square test for trend as appropriate. Comparisons of different categorical variables were tested by contingency tables-based chi-square test. We have further analysis the students who went through both in the 2019 and 2020 examinations for evaluating the VI incidence during the COVID-19 pandemic. Results: More than 1,057,061 students were involved in our study, among whom 276,638(54.90%) out of 503,874 students in Guangzhou suffered from VI during the COVID-19 compared with 296,940(53.68%) visually impaired students (Total tested participants=553,187) before the COVID-19 pandemic. During the pandemic, the overall prevalence of VI actually showed an increased age tendency and reached the highest level in the 17[81.19%, 95%Confidence interval(CI):80.72% to 81.66%] and the 18(82.05, 95%CI: 81.46% to 82.64%) age groups. Rapid growth was detected among students aged between 9 and 16 years old(raised by 46.99%) while older students were more likely to get moderate and severe VI than younger ones. Students involved in more screen-based activities[(64.83%, 2019);(66.59%, 2020)] appeared to have a higher prevalence of VI than those involved in less[(49.17%, 2019);(49.26%, 2020)]. Conclusion A rising trend of VI among students was detected before and during the COVID-19 pandemic. Moreover, the pandemic appeared to be associated with a rapid VI shift in younger and boy populations. Potential danger may arise when public health emergencies occur in the school, and more effort should be made to improve students’ vision.